Subtle concentration changes in zinc hold the key to fibrillation of α-synuclein: an updated insight on the micronutrient’s role in prevention of neurodegenerative disorders - Banik, Samudra Prosad; Bagchi, Debasis; Banerjee, Pradipta; Chakraborty, Sanjoy; Bagchi, Manashi; Bose, Chaitali; De, Debasmita; Saha, Sreemoyee; Chakraborty, Sudipta (Frontiers in Molecular Biosciences, 2025)
Misfolded proteins have been found to be at the core of an increasing number of cognitive ailments. α-synuclein, a resident chaperone of the neurosynaptic cleft has been implicated in a major share of these neurodegenerative diseases. Over the years, a daunting task for researchers has been the identification of the complex set of conditions which govern the Substantia nigra microenvironment for transformation of α-synuclein from a functional and grossly structureless chaperone to toxic cross-β fibrils. An abundance of Reactive Oxygen Species and a drop in pH of the solvent have been identified to be the key drivers of the fibrillation process which is initiated by Liquid-Liquid phase separation of α-synuclein droplets. Zinc is a significant micronutrient of the human body integral to the proper functioning of the nervous system as well as holistic cognitive development. Many recent studies have deciphered that metal ions including zinc facilitate the fibrillation of α-synuclein by shielding negative charges at the C terminus of the protein. Zinc preferentially binds to Asp121 at the C terminus and His50 at the N terminus to promote fibrillation. On the contrary, zinc has many protective roles to retard fibrillation of the protein at the same time. It downregulates ROS and assists chaperones which prevent non-native aggregation of α-synuclein. The ability of zinc to bind preferentially to α-synuclein coupled with the advent of ultrasensitive detection technologies such as the Surface Enhanced Raman Spectroscopy has led to the prospects of zinc-oxide nanoparticles as effective tools to probe the α-synuclein-based biomarker for early detection of protein aggregates in the body fluid. This review summarizes the significant mechanistic findings which has facilitated our understanding of the fibrillation of α-synuclein, the precise role and mechanism of zinc involved therein and the prospects of using zinc in designing efficient tools for diagnosis of Parkinson’s Disease and other synucleinopathies.